A field-oriented control method using the virtual currents for the induction motor drive - Cuong Dinh Tran; Tien Xuan Nguyen; Phuong Duy Nguyen (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
An improving field-oriented control technique without current sensors is proposed to control rotor speed for an induction motor drive. The estimated stator currents based on the slip frequency are used instead of feedback current signals in the field-oriented control (FOC) loop. The reference signals and the estimated currents through computation steps are used to generate the control voltage for the switching inverter. Simulations were performed in Matlab/Simulink environment at rated speed and low-speed range to demonstrate the method's feasibility. Through simulation results, the FOC method using virtual sensors has proved its effectiveness in ensuring the stable operation of the induction motor drive (IMD) over a wide speed range.